2008
DOI: 10.1889/1.2896319
|View full text |Cite
|
Sign up to set email alerts
|

Thermally adaptive response‐time compensation for LCDs

Abstract: Abstract— This paper presents thermally adaptive driving (TAD) technology for response‐time compensation (RTC) of an LCD with an integrated sensor. The TAD system is comprised of an analog sensor, an analog sensor signal conditioning, and a digital feedback algorithm. The integrated thermal sensor provides accurate temperature measurement of the liquid‐crystal layer. The TAD controller has an eight‐step look‐up‐table (LUT) and compensates response time based on the panel temperature. The TAD system reduces res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…It is reported that the overdrive values are highly dependent on the temperature. 15,16 Accurate prediction of responses enables engineers to obtain overdrive values for all transitions. We have been able to accurately predict the responses regardless of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the overdrive values are highly dependent on the temperature. 15,16 Accurate prediction of responses enables engineers to obtain overdrive values for all transitions. We have been able to accurately predict the responses regardless of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-E Test enables collecting key parameters of LC models, showing that design models can be verified with actual parameters of cell panels by using Cell-E Test. Parameters of LCD models vary with respect to temperature [15][16][17]. Cell-E Test can be also used for evaluating temperature dependency of LC by measuring under multiple temperature conditions.…”
Section: Resultsmentioning
confidence: 99%